Identification of risk factors: a comparison of conventional and Islamic stocks - Hanif, Muhammad (Technological and Economic Development of Economy, 2025)
The study identifies the difference in the long-run risk factors for Conventional Capital Market (CCM) and Islamic Capital Market (ICM) in the post-Shari’ah-screening era in an emerging market. The sample includes macroeconomic variables representing the real sector (industrial production), money market (interest rate), international market (exchange rate) and external sector (exports and workers’ remittances) and two market indexes for 164 Months (01/10–08/23). Johansen cointegration and Granger causality tests are applied to document the evidence. Results support the integration of market indexes with macroeconomic indicators; however, market indexes lack mutual integration in the long run. The integrated group of variables differs slightly for ICM (exchange rate and industrial production) and CCM (industrial production). The real sector activity is reflected in the market, while the monetary sector is missing. The behaviour of the Islamic market is in line with the theory – a reflection of the real sector and lack of integration with interest rates. We recommend three policy actions, including improved facilitation of industrial production, prudent management of exchange rate, and a balanced monetary policy, as theory suggests the usefulness of stock indicators for monetary policymaking. The comparative study on macroeconomic risk factors in an emerging market enhances the understanding of a market with dual indexes, including CCM and ICM.First published online 31 March 2025